Adherence and Tolerability of Alzheimer's Disease Medications: A Pragmatic Randomized Trial. Issue 7 (14th March 2017) - Campbell, Noll L.; Perkins, Anthony J.; Gao, Sujuan; Skaar, Todd C.; Li, Lang; Hendrie, Hugh C.; Fowler, Nicole; Callahan, Christopher M.; Boustani, Malaz A.
Abstract : Background/Objectives: Post‐marketing comparative trials describe medication use patterns in diverse, real‐world populations. Our objective was to determine if differences in rates of adherence and tolerability exist among new users to acetylcholinesterase inhibitors (AChEI's). Design: Pragmatic randomized, open label comparative trial of AChEI's currently available in the United States. Setting: Four memory care practices within four healthcare systems in the greater Indianapolis area. Participants: Eligibility criteria included older adults with a diagnosis of possible or probable Alzheimer's disease (AD) who were initiating treatment with an AChEI. Participants were required to have a caregiver to complete assessments, access to a telephone, and be able to understand English. Exclusion criteria consisted of a prior severe adverse event from AChEIs. Intervention: Participants were randomized to one of three AChEIs in a 1:1:1 ratio and followed for 18 weeks. Measurements: Caregiver‐reported adherence, defined as taking or not taking study medication, and caregiver‐reported adverse events, defined as the presence of an adverse event. Results: 196 participants were included with 74.0% female, 30.6% African Americans, and 72.9% who completed at least twelfth grade. Discontinuation rates after 18 weeks were 38.8% for donepezil, 53.0% for galantamine, and 58.7% for rivastigmine ( P = .063) in the intent to treat analysis. Adverse events and cost explained 73.1% and 25.4% of discontinuation. No participants discontinued donepezil due to cost. Adverse events were reported by 81.2% of all participants; no between‐group differences in total adverse events were statistically significant. Conclusions: This pragmatic comparative trial showed high rates of adverse events and cost‐related non‐adherence with AChEIs. Interventions improving adherence and persistence to AChEIs may improve AD management. Trial Registration: Clinicaltrials.gov: NCT01362686 (https://clinicaltrials.gov/ct2/show/NCT01362686 ).